HUBUNGAN LAMA MENJALANI HEMODIALISA DENGAN STATUS DEPRESI PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Sepadha Putra Sagala, Deddy; Hutagaol, Aureliya; Ritonga, Imelda Liana; Anita, Sabrina Iwanda; Zamago, Jonta Hendrik Pratama (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Hemodialysis is one of the treatments that can be carried out in patients with chronic kidney failure where hemodialysis can be a replacement therapy for kidney function. However, a long period of undergoing hemodialysis can affect a person's psychosocial factors due to dependence and limitations in carrying out activities. The aim of this study was to determine the relationship between the length of time undergoing hemodialysis and the depression status of chronic kidney failure patients at the Imelda Workers Indonesia General Hospital, Medan. This type of research is quantitative research with correlational methods and a cross-sectional approach design. This research was conducted in July-August 2023 in the Hemodialysis Room at the Imelda General Hospital for Indonesian Workers in Medan. This research used a Probability sampling technique using the Multistage Sampling method, namely the stratified sampling method in the first stage then the Quota sampling method in the next stage. second, so that the total research sample is 60 respondents. The instrument used in this research is a questionnaire that refers to the Beck Depression Inventory (BDI-II) to determine depression status. Data analysis used univariate and bivariate analysis with statistical tests (Chi-Square Test) in the SPSS application. The research results in this study show the results of the Chi-Square statistical test with a significant (p) value of 0.001 or p<0.05, meaning it exists. There is a relationship between the length of time undergoing hemodialysis and depression status in chronic kidney failure patients at the Imelda Workers Indonesia General Hospital, Medan. The conclusion that we got was that the tendency for depression increased in clients who had just undergone hemodialysis. The longer you undergo hemodialysis, the lower your depression status.